Co-education in the teaching of technical sciences in higher education - Daminova Yulduz (Genius Journals, 2023)
The article provides experience in the implementation of innovative types of training, which is used in the process of teaching technical disciplines. The paper reflects innovative forms of education that will allow teachers to more activate the cognitive activity of students.
Keywords: interactive form of education; innovative form of education; technical disciplines